2018
DOI: 10.1016/j.heliyon.2018.e00803
|View full text |Cite
|
Sign up to set email alerts
|

Incidental extraspinal findings in the lumbar spine during magnetic resonance imaging of intervertebral discs

Abstract: PurposeTo calculate the frequencies of incidental extraspinal findings and incidentally detected congenital anomalies or anatomical differences in the lumbar spine on magnetic resonance imaging (MRI) scans of intervertebral discs.Materials and methodsA total of 379 lumbar spine MRI cases were prospectively investigated in the period spanning from August 2016 to January 2018. Both 1.5 and 0.35 Tesla MRI units (Toshiba and Siemens Medical Systems) were used to examine patients with clinically suspected intervert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
(40 reference statements)
4
6
0
2
Order By: Relevance
“…This series, with a larger sample size compared to the previous series, showed that the prevalence of ESFs is 31.1%. This prevalence was close to several other studies 5 , 6 , 8 . However, it was lower than that reported by Quattrocchi et al 3 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This series, with a larger sample size compared to the previous series, showed that the prevalence of ESFs is 31.1%. This prevalence was close to several other studies 5 , 6 , 8 . However, it was lower than that reported by Quattrocchi et al 3 .…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, underreporting of ESFs, especially those of clinical significance can adversely affect subsequent patient management. In addition, it can raise ethical and legal concerns for the reading radiologists 3 , 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…[7] and Zidan et al . [13] , the IFs in the thyroid gland were 17.4% and 6.3%, respectively, while IFs in the thyroid gland in the present research were 3.3% in the form of thyroid goiter (1.7%), thyroid nodule (0.8%), and cervical cyst (0.8%) [Table 2]. This inequality in the incidence rates could be validated based on their enormous population study related to our research.…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, the incidence rate of a thyroid goiter in thoracic spine MRI scans was 1.7% [Table 2], which is lower than the rate 4.6% described by Zidan et al . [13] This might be due to the fact that our research focused on the thoracic spine but that is of Zidan et al . [13] focused on the cervical spine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation